Estudo das interações fitoplâncton-protozooplâncton no reservatório de Barra Bonita, SP, com ênfase na toxicidade de microcistinas - Araujo, Laryssa Melo Rosa (Universidade Federal de São Carlos, 2009)
The increasing eutrophication of aquatic environments, resulting from the human activities, is related to cyanobacterial blooms that are described, all over the world, as the agents causing toxicity and death in humans, domestic and wild animals. Recently, studies are being conducted aiming to prove the possibility of the biotransference of the cyanobacterial toxins to the trophic web and their associated effects. Protozoans are very important organisms to the aquatic food web and can be useful as indicators in water quality assessment. The present study evaluated, during cyanobacteria bloom events in Barra Bonita reservoir (SP), the intra and extracellular cyanotoxin levels (microcystin LR) and also phyto and protozooplanktonic populations. Besides, it was also evaluated, in laboratory experiments, the effects of the cyanotoxins obtained from cultures of Microcystis and from material collected in Barra Bonita reservoir on the protozoan Paramecium caudatum. Due to the eutrophication degree of the studied reservoir, the cianobacteria, specially Microcystis (M. aeruginosa, M. protocystis and M. panniformes) and Pseudanabaena mucicola, were the dominant phytoplanktonic organisms. In this work it was registered only the concentrations of microcystin LR. The concentrations of this toxin were median among those found for other Brazilian aquatic environments where it was detected more than one cyanotoxin variant. Halteria grandinella and Vorticela aquadulcis were the dominant protozoans in the environment during the cyanobanterial bloom events. The protozooplanktonic densities and species composition were lower than those found in the literature for environments with the same trophic status, indicating that the protozoan seem to be negatively affected by the cyanobacterial blooms and cyanotoxins (microcystins) detected in the samples. Samples from Microcystis cultures and from the reservoir demonstrated to be toxic to P. caudatum, although they were more tolerant to the semi purified extracts from cultures than to the environmental samples.
Keywords: Limnologia; Ecotoxicologia; Fitoplâncton; Protozoário; Eutrofização; Microcistina; Ecotoxicidade; Eutrophication; Phytoplankton; Microcystin; Protozooplankton; Ecotoxicity; CIENCIAS BIOLOGICAS::ECOLOGIA